Crystallochemical Study of Kaolinitic Minerals from Anambra And Ebonyi States of Southeastern Nigeria - C.J.O, Anarado,; A.N, Eboatu,; C.E, Anarado,; C.I., Egwuatu, (IJRDO-Journal of Applied Science, 2016)
The major deposits of Kaolinitic mineral were sampled, with the aim of studying possible solid solution, ionic substitution, and thus, ultimately understanding the the nature and sizes of nanoparticles in the mineral deposits. Powder X-ray Diffraction Analysis, X-ray Flourescence analysis and Physical tests were used to study them. Kaolinite and Quartz were the major phases in the raw Anambra Kaolin, while the Ebonyi Kaolin had Kaolinite, Quartz, Cristobalite, Montmorillonite and Goethite as major phases. The quartz were deposited in hexagonal crystalline structure, with cell parameters : a- 4.91239A, b-4.91239A, c-5.40385A. The Kaolinite had Monoclinic structure, with cell parameters: a5.16000A, b-8.95232A, c-7.39000A. Cristobalite had Cubic structure, with a,b,c,=7.16000A. Montorillonite had hexagonal structure, with a-5.21000A, b5.21000A, c-22.00000A. Goethite had Orthorhombic structure, with a-4.61880A, b-9.95280A, c-3.02360A. The Specific Gravity of the Anambra deposite was 2.2, while that of Ebonyi was 2.6. Both had relatively low Moh’s hardness value of 1.0. While the Anambra deposit showed white streak, the Ebonyi deposit showed Yelllowish brown streak. The Anambra deposit had the major oxides as -Al2O3 = 27.71%, SiO2 = 65.76, giving a ratio of 2.37, while the Ebonyi deposit had Al2O3 =5.22, SiO2 =77.05, with a ratio of 14.76. Both ionic substitution and solid solution occurred in the Ebonyi deposit. Montmorillonite has replaced some Quartz in its hexagon structure, instead of the usual Monoclinic structure. The Kaolinite also had a Triclinic structure instead of hexagonal structure expected. The industrial application of these minerals would be significantly impacted by the nano-structural changes.